Kinetic-Based Reactivity for Michael Acceptors: Structural Activity Relationships and Its Relationship to Excess Acute Fish Toxicity - Schultz, Terry W.; Aptula, Aynur O. (Bulletin of environmental contamination and toxicology, 2016)
Acute aquatic toxicity is divided into the “physical” mode governed by weak, non-covalent interactions and the “chemical” mode governed by covalent reactions. The potency of chemical interactions is typically expected to be greater than that for physical ones. This enhanced potency is called “excess” toxicity. As databases have become complex, substances thought to elicit a chemical mode reveal a lack of excess toxicity. One mechanism where the latter is prevalent is Michael-type addition. A series of α-β-unsaturated substances were evaluated for reactivity. Second order rate constants ( k ′) were calculated (M −1 s −1 ) and found to vary from >4000 to <0.0003. The electron-withdrawing capacity of the polar group impacts k ′ values; the sequence is nitro > carbonyl or sulfone ≫ sulfoxide, nitrile or amide. When the α-carbon and/or the β-carbon of the π-system are substituted, the k ′ value is sharply reduced. Excess toxicity is associated with k ′ values >0.01 (M −1 s −1 ).